Evaluación técnica del desempeño de los portadores energéticos que se usan en el Hospital Isidro Ayora de la ciudad de Loja. - Carrera Paladines, José Mauricio (2012)
Because traditionally the priority of the institutions of health has been the attention to the patient, for a lot of time importance has been subtracted to the problems related with the energy payees and with the environment, being been able to create in many cases inefficient and elevation of the derived costs of the inadequate handling of these aspects. This study is carried out by the interest of the hospital "Isidro Ayora of Loja" (HIAL) of optimizing the costs related with the use of energy payees, as well as to have an attitude responsible with the community environment. The same one was carried out with the support of the administrative authorities of the HIAL who they facilitated necessary information for the realization of this report. During this period they were carried out technical visits to different services of the Hospital, carrying out interviews and observations. The analysis of the expenses for energy payees' concept and it dilutes, it shows the necessity to work in the search of reservations in the three main sources of expenses that are: electricity, the diesel and the water. He settled down by means of the characterization of the energy payees of the year 2009 - 2010 that the electricity is the main energy source and that he/she has the biggest weight in the costs of operation of the entity, for it should be lent it main interest to this source and to make the possible thing to determine the saving opportunities that can be applied for this energy payee